Сравнение систем информационной безопасности на основе энтропийного подхода к определению риска - Мохор, В.В.; Цуркан, В.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The approach to an estimation of information security risks safety with use of an
entropy of a probability distribution is considered.